2021
DOI: 10.3390/life11050454
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Gene Phylogeny and Morphology Reveal Haplohelminthosporium gen. nov. and Helminthosporiella gen. nov. Associated with Palms in Thailand and A Checklist for Helminthosporium Reported Worldwide

Abstract: Palms (Arecaceae) are substrates for a highly diverse range of fungi. Many species are known as saprobes and many are important plant pathogens. Over the course of our studies of micro-fungi from palms in Thailand, two new taxa were discovered. Morphological characteristics and phylogenetic analyses of combined ITS, LSU, SSU, and tef1-α sequence data revealed their taxonomic positions within Massarinaceae. There are currently ten genera identified and accepted in Massarinaceae, with the addition of the two new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 92 publications
0
17
0
Order By: Relevance
“…For instance, H. cynodontis was reassigned to the genus Bipolaris (Pleosporaceae, Pleosporales) due to the production of sympodial conidiogenous cells and by having darkly pigmented conidiogenous loci [46]. Recently, Konta et al [7] accepted 216 Helminthosporium species, however many species are identified only based on morphological studies, and only 25 species have sequence data. The lack of a large amount of molecular data is mainly because most species were introduced before the advent of Sanger sequencing.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For instance, H. cynodontis was reassigned to the genus Bipolaris (Pleosporaceae, Pleosporales) due to the production of sympodial conidiogenous cells and by having darkly pigmented conidiogenous loci [46]. Recently, Konta et al [7] accepted 216 Helminthosporium species, however many species are identified only based on morphological studies, and only 25 species have sequence data. The lack of a large amount of molecular data is mainly because most species were introduced before the advent of Sanger sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, H. hispanicum is fungicolous and grows on old conidiomata of Juglanconis juglandina [8], whereas H. chengduense (UESTCC 22.0024) is saprobic on decaying wood in damp environments. Konta et al [7] summarized the morphological characteristics of 216 Helminthosporium species. Among them, only H. asterinum, H. longisinuatum, and H. makilingense produce larger conidia than H. chengduense UESTCC 22.0024.…”
Section: On557758 On557746 On557752 On563074 On600599mentioning
confidence: 99%
See 3 more Smart Citations